Ratiometric sensing of anions by tetraamide-based receptors bearing hydroxy groups from serine and threonine residues. Issue 10 (9th March 2016) - Kondo, Shin-ichi; Matsuta, Yuka
Graphical abstract: Abstract: Tetraamide-based receptors bearing hydroxy groups from serine and threonine side chains showed suitable ratiometric fluorescence responses upon the addition of basic oxoanions such as phosphate by pendant pyrenyl groups in aqueous MeCN. Receptor3 is the first example of an artificial anion receptor bearing threonine residues as recognition sites.